Examining e-service quality influence on e-loyalty: A mediating effects of e-satisfaction and e-trust for Tokopedia users - Wulandari, Anggun; Thabrani, Gesit (Marketing Management Studies, 2023)
This research will focus on users of the Tokopedia online shopping application in the city of Padang. The objective of this research is to investigate how Electronic Service Quality (E-Service Quality) influences Electronic Loyalty (E-Loyalty), and to explore the involvement of Electronic Satisfaction (E-Satisfaction) in this relationship. and Electronic Trust (E-Trust) as mediating variables. A total of 250 respondents were sampled for this research. Data was processed using SmartPLS and collected through questionnaires online. The research findings indicate that (1) Electronic Service Quality significantly and positively influences the e-satisfaction. (2) Electronic Service Quality has a significant and positive impact on electronic trust. (3) Electronic Service Quality has a significant positive impact on e-loyalty. (4) Electronic Satisfaction has a significant and positive impact on e-loyalty. (5) Electronic Trust has a significant and positive impact on e-loyalty. (6) Electronic Trust has a significant and positive impact on e-satisfaction. (7) E-Service Quality has a significant and positive effect on e-satisfaction with e-trust as a mediation. (8) E-Service Quality has a significant and positive impact on e-loyalty, with e-satisfaction as a mediation. (9) Electronic Service Quality has a significant and positive impact on e-loyalty with e-trust as a mediation.